STRUKTUR PENYAJIAN TARI JEPIN RAJUT SEMPURONG DI DESA SERIMBU KECAMATAN AIR BESAR KABUPATEN LANDAK - Kiki Andriani; Regaria Tindarika; Yudhistira Oscar Olendo (Universitas Tanjungpura, 2021)
AbstractThis research is motivated because of the uniqueness of the jepin rajut sempurong dance in terms of dance movements, accompaniment music, dance gender, property, floor patterns, as well as clothing and make-up. This research uses descriptive methods, qualitative research forms and a choreographic approach. Sources of research data in the form of observations, interviews, and documentation of sources, namely Rahmani Hassan, Muslimin and Dedi. The technique of testing the validity of the data uses triangulation of sources with data analysis techniques that are structured and analyzed systematically. Based on the data analysis, it is concluded that the structure of the presentation of the jepin rajut sempurong Dance is serimbu village. Jepin rajut sempurong is a spectacle dance in serimbu village, this dance is performed by 9 dancers, 1 male dancer as a perfect dance, the musical instruments used to accompany thisdance are lute and tambourine, kompang and rhyme rhyme, jepin rajut sempurong dance uses rope properties, this dance uses a vertical and circular floor pattern, this dance uses a vertical and circular floor pattern, this dance uses realist make-up,clothes worn by female dancers with a traditional bay shirt, black cloth pants, skullcap, and cloth, songket.Keywords: Presentation structure, Jepin Rajut Sempurong dance